Lysosomal Fusion: An Efficient Mechanism Increasing Their Sequestration Capacity for Weak Base Drugs without Apparent Lysosomal Biogenesis - Skoupa, Nikola; Dolezel, Petr; Mlejnek, Petr (Biomolecules, 2020)
Lysosomal sequestration of anticancer therapeutics lowers their cytotoxic potential, reduces drug availability at target sites, and contributes to cancer resistance. Only recently has it been shown that lysosomal sequestration of weak base drugs induces lysosomal biogenesis mediated by activation of transcription factor EB (TFEB) which, in turn, enhances their accumulation capacity, thereby increasing resistance to these drugs. Here, we addressed the question of whether lysosomal biogenesis is the only mechanism that increases lysosomal sequestration capacity. We found that lysosomal sequestration of some tyrosine kinase inhibitors (TKIs), gefitinib (GF) and imatinib (IM), induced expansion of the lysosomal compartment. However, an expression analysis of lysosomal genes, including lysosome-associated membrane proteins 1, 2 (LAMP1, LAMP2), vacuolar ATPase subunit B2 (ATP6V1B2), acid phosphatase (ACP), and galactosidase beta (GLB) controlled by TFEB, did not reveal increased expression. Instead, we found that both studied TKIs, GF and IM, induced lysosomal fusion which was dependent on nicotinic acid adenine dinucleotide phosphate (NAADP) mediated Ca2+signaling. A theoretical analysis revealed that lysosomal fusion is sufficient to explain the enlargement of lysosomal sequestration capacity. In conclusion, we demonstrated that extracellular TKIs, GF and IM, induced NAADP/Ca2+ mediated lysosomal fusion, leading to enlargement of the lysosomal compartment with significantly increased sequestration capacity for these drugs without apparent lysosomal biogenesis.
Keywords: signální transdukce; Gefitinib; Lysosomes; Protein-Tyrosine Kinases; Organelle Biogenesis; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Humans; lidé; K562 Cells; transkripční faktory BHLH-Zip; Drug Resistance, Neoplasm; buňky K562; chemorezistence; gefitinib; tyrosinkinasy; lyzozomy; imatinib mesylát; Antineoplastic Agents; biogeneze organel; Cell Line, Tumor; nádorové buněčné linie; Imatinib Mesylate; Signal Transduction; protinádorové látky